A transdisciplinary approach to the economic analysis of the European Water Framework Directive - Martin Ortega, J.; Perni, A.; Jackson-Blake, L.; Balana, Bedru; Mckee, A.; Dunn, S.; Helliwell, R.; Psaltopoulos, D.; Skuras, D.; Cooksley, S.; Slee, B. (Elsevier, 2015)
The EuropeanWater Framework Directive(WFD) prescribes economic principles to achieve its ecological targets. The aim is to establish cost-effective measures to attain good ecological status and assess whether the costs of these measures are justifiable in view of the benefits they provide. The complex nature of water problems requires flexible decision-making embracing a diversity of ‘knowledges’. Here, natural and social scientist worked together in an integrated approach ‘ground-tested’ through local stakeholders' knowledge and views. The aims were to: (1) develop a set of steps for implementing this transdisciplinary approach, and (2) critically reflect on the challenges of integrating different strands of knowledge to the specific context of the economics of the WFD. Thiswas tested at a sub-catchment in Scotland. Hydro-chemicalmodelswere used to simulate effectiveness of phosphorous pollution mitigation measures, which was then incorporated into a cost-optimization model. Costs were compared with benefits resulting from water quality improvements. This analysis was accompanied by an iterative local stakeholder consultation process. The research further analysed whether selected measures are ‘future-proof’ in view of climate and land-use changes. Results are used to help set the research agenda for more practical specification of economically sound and socially acceptable ways to deliver theWFD.